Criminal liability for perpetrators of the crime of lobster cultivation without a permit (Case Study Decision Number: 5/Pid.Sus-PRK/2021/PN Jkt.Utr) - Setiawan, Buddy; Juwita, Juwita (CV. Publikasi Indonesia, 2025)
There are still immoral individuals who do not comply with existing regulations, one of which involves the illegal transportation of baby lobster larvae without a Fisheries Business License (SIUP). This is reflected in the case study of the criminal fisheries ruling, which has become final and binding, namely the ruling on the crime of Lobster Cultivation Without Permission in the North Jakarta District Court ruling number 5/Pid.Sus-Prk/2021/PN Jkt.Utr. This research aims to analyze the criminal responsibility of the perpetrators in the lobster cultivation crime based on this ruling and to examine the judge's considerations in imposing criminal sanctions. The research uses a normative legal study method, which examines the system of legal norms through legislation, court decisions, and doctrines. The research findings show that the criminal responsibility of Defendants I and II is joint responsibility in the fisheries crime, as they were not the owners but were instructed by the owners of the baby lobster larvae, who are still being searched. The legal basis applied is Article 88 Jo Article 16 paragraph (1) of Law No. 11 of 2020 on Job Creation, with the judge's considerations covering legal, sociological, and philosophical aspects.